Project-based learning course design : a service design approach - Lima, Rui M. (2012)
Engineering education is becoming increasingly focused on developing competences, creating meaningful learning experiences and paying special attention to professional profiles as required by accreditation bodies. Project‐based Learning (PBL) is one of the approaches that is regarded as an adequate response to the current demands of engineering education. PBL is, by definition, based on interdisciplinary integration, so the design process is based on complex interdisciplinary requirements and interactions demanding systematic and standardized approaches. This work aims to develop a service design framework for the development of a project‐based curriculum, which is regarded as a specific interpretation of service design. A service design approach based on structure, process and outcome dimensions is related with a set of methodological dimensions. This framework is connected with curriculum development levels to build a design model for PBL courses. Finally, the model is applied to a PBL curriculum design process in a Production Engineering graduate degree. Keywords: service; service design; project‐based learning; curriculum